Electrochemical reduction of dehydroamino acids: Synthesis and photophysical properties of beta,beta-diarylalanines - Ferreira, Paula M. T. (2011)
Several beta,beta-disubstituted dehydroalanines were prepared from beta,beta-dibromo or beta-bromo, beta-substituted dehydroalanines and aryl boronic acids using a Suzuki-Miyaura cross-coupling reaction. The electrochemical behaviour of these compounds was studied by cyclic voltammetry. All compounds studied showed similar reduction potentials and these were similar to the peak potential of the methyl ester of N-tert-butoxycarbonyl dehydrophenylalanine. Thus, the presence of a second aryl moiety in the dehydroalanine scaffold does not significantly change the reduction potential. Controlled potential electrolysis were preformed at the cathodic peak potential in the presence of triethylammonium chloride as proton donor. The only products isolated in good to high yields were the corresponding beta,beta-diarylalanines. This reaction was also carried out using a dipeptide containing a beta,beta-diaryldehydroalanine to give a 1:1 diastereomeric mixture of the reduction product. The photophysical properties of two of the beta,beta-diaryldehydroalanines and of the corresponding beta,beta-diarylalanines were studied in three solvents of different polarity. The beta,beta-diaryldehydroalanines show low fluorescent quantum yields (< 9%) due to the conjugation of the aromatic moieties with the alpha,beta-double bond and with the carbonyl group, which favours the non-radiative deactivation pathways. The absence of conjugation in the reduction products leads to a significant increase in the fluorescence quantum yields. These results show that the beta,beta-disubstituted alanines could be used as fluorescent markers.